2015
DOI: 10.1186/1546-0096-13-s1-p141
|View full text |Cite
|
Sign up to set email alerts
|

Severe immune dysregulation with neurological impairment and minor bone changes in a child with spondyloenchondrodysplasia due to two novel mutations in the ACP5 gene

Abstract: Spondyloenchondrodysplasia (SPENCD) is a rare skeletal dysplasia, characterized by metaphyseal lesions, neurological impairment and immune dysregulation associated with lupus-like features. SPENCD is caused by biallelic mutations in the ACP5 gene encoding tartrate-resistant phosphatase. We report on a child, who presented with spasticity, multisystem inflammation, autoimmunity and immunodeficiency with minimal metaphyseal changes due to compound heterozygosity for two novel ACP5 mutations. These findings exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…However, variability was observed, with subtle manifestations in some cases, and two patients demonstrating only metaphyseal or vertebral changes. A mild skeletal phenotype, with only ‘discrete metaphyseal changes’ at the wrist was also reported by Girschick et al [ 17 ]. In keeping with this radiological diversity, a height within the normal range, particularly at a young age, does not exclude the diagnosis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, variability was observed, with subtle manifestations in some cases, and two patients demonstrating only metaphyseal or vertebral changes. A mild skeletal phenotype, with only ‘discrete metaphyseal changes’ at the wrist was also reported by Girschick et al [ 17 ]. In keeping with this radiological diversity, a height within the normal range, particularly at a young age, does not exclude the diagnosis.…”
Section: Discussionsupporting
confidence: 68%
“…1 A diagram illustrating the distribution of all reported ACP5 pathogenic variants. Below the gene diagram data are shown from this study with number of alleles per variant observed in parentheses; in addition pathogenic variants not identified in this study, but previously reported by Lausch et al [ 8 ] and Girschick et al [ 17 ] are depicted above the gene diagram …”
Section: Resultsmentioning
confidence: 86%
“…Spondyloenchondrodysplasia (SPENCD, OMIM 607944) is a rare autosomal recessive skeletal dysplasia which is characterized with neurological involvement and immune dysfunction (25). SPENCD is an interferonopathy.…”
Section: Discussionmentioning
confidence: 99%
“…SPENCD (OMIM 607944) is a rare autosomal recessive skeletal dysplasia, characterized by neurological involvement and immune dysfunction (26). SPENCD is a member of the interferonopathy group.…”
Section: Discussionmentioning
confidence: 99%